The effect of the generative learning model on the student critical thinking ability in environmental conservation topic - Fairuz Mumtaz; Sjaifuddin Sjaifuddin; Adi Nestiadi (Jurnal Pijar Mipa, 2023)
The low level of students' critical thinking ability makes students need help understanding science concepts. The application of an interactive learning model can be a solution to this problem. This research aims to analyze the effect of the Generative learning model on the critical thinking ability of 7th graders in Environmental conservation Materials. The research method used is the Quasy Experiment method carried out in class VII junior high school SMP Mutiara Insani Tangerang. Students' critical thinking abilities are measured by a written test instrument in the form of essay questions made according to indicators of critical thinking ability that have been adjusted as many as ten questions tested for validity and reliability. The selected experimental class comes from a population that is normally distributed, has a homogeneous variance, and has the same mean. The research results show that the experimental class with the Generative Learning model and the control class with the Discovery Learning model are normally distributed. Hypothesis testing is done by t-test, and the significance level is based on the results of the Posttest; there is a significant influence of the Generative Learning learning model on the critical thinking ability of class VII students. In conclusion, the Generative Learning Learning Model affects the Critical Thinking Ability of 7th graders Students in Environmental Conservation material.